Pakistan : the us, geopolitics and grand strategies - Butt, Usama; Schofield, Julian ([S.l.] : Pluto Press, 2012)
The killing of Osama bin Laden highlighted the tense relationship between the US and Pakistani governments. This book considers the evolving nature of this relationship and Pakistan's place within the global order. Whereas standard accounts focus on the US-Pakistan relationship in isolation, Pakistan: The US, Geopolitics and Grand Strategies provides a broader geopolitical perspective. It analyzes Pakistan's relations with the US after a decade of the War on Terror as well as Pakistan's regional relations, which provides the reader with a complete understanding of Pakistan's interests. Contributions from experts in both Pakistan and the West mean that this book will be vital reading for anyone seeking to understand this troubled nation.
Keywords: Geopolitics; International relations; Pakistan; United States